Kolon Kanserinde Etkilenen Yolak Alt Ağlarini Ve Kümelenmelerini Belirlemek için Yeni Bir Yöntem - Göy, Gökhan; Ünlü Yazici, Miray; Bakir-Güngör, Burcu (Institute of Electrical and Electronics Engineers Inc., 2019)
Nowadays new technological developments that play an important role in the production of big data have brought about the interpretation, sharing and storage of data related to complex diseases. Combining multi-omic data in different molecular levels is potentially important for understanding the biological origin of complex diseases. One of these complex diseases is cancer of different types, which has one of the highest causes of death worldwide. The integration of multiple omic data in the framework of a comprehensive analysis and identification of relevant pathways contribute to the development of therapeutic approaches related to disease. In this study, RNA and methylation data (genes and p values) of colon adenocarcinoma were obtained from TCGA data portal and combined with Fisher's method. While protein subnetworks affected by the disease were identified by using subnetwork algorithm, pathways related to the disease and genes associated with these pathways were determined by functional enrichment analysis. Using gene-pathway relationship matrix, kappa scores of pathways were determined by similarity calculation. In this way, the pathways were clustered according to the hierarchically optimal number, as a result, the most important pathway clusters and related genes that are effective in disease formation identified. © 2020 Elsevier B.V., All rights reserved.
A New Method to Identify Affected Pathway Subnetworks and Clusters in Colon Cancer
Unlu Yazici, Miray/0000-0001-8165-6164;
Keywords: Functional Enrichment; Kappa Score; Pathway; Pathway Clustering; Subnetwork Identification; Alkylation; Digital Storage; Genes; Functional Enrichments; Kappa Score; Pathway; Pathway Clustering; Sub-Network; Diseases